RESULTADOS PERINATAIS NA GRAVIDEZ EM ADOLESCENTES PRECOCES NO MUNICÍPIO DE SÃO LUÍS MA - Correia, Alcioneyaria da Silva (2012)
Pregnancy in early adolescence (10-14 years), little studied, has been associated with adverse obstetric outcome. Objective: To identify the socioeconomic and demographic characteristics of early adolescents, as well as verify the association of pregnancy in this age group with perinatal outcomes. Methods: This was a cross-sectional study, descriptive and analytical and is part of a birth cohort in two Brazilian cities. The sample was stratified with proportional sharing of the number of births. Questionnaires were administered in the form of an interview , in women after childbirth , to evaluate aspects related to the newborn and the mother , such as identification data , socioeconomic and demographic factors , lifestyle habits , previous morbidities and current pregnancy characteristics and pregnancy , prenatal , labor and birth . We evaluated 5161 births in the city of São Luís in 2010. Results: The analysis was multivariate stepwise logistic regression. Among the births analyzed, 2.21 % occurred in early adolescent mothers. A higher proportion had income from 1 to 2 wages ( 29.46% ) , 66.40 % were unemployed, 85.54 % of deliveries were in public hospitals , 14.02 % of children born preterm and 16.50% of women had hypertension in pregnancy . Only 2.03% did not undergo prenatal 13.02% consumed beer during pregnancy and 15.79 % of the adolescents had early preterm deliveries. No association was observed between age and early teen no perinatal outcome, except the range 16 to 19 years who presented the outcome as protection for small for gestational age (SGA). Conclusions: The study population had sociodemographic characteristics (income and low education) similar to most of the population of São Luís, but there was a decrease in the prevalence of teenage pregnancy in the previous decade. It was observed that the mother's age (early teen ) was not a risk factor for adverse perinatal outcomes .